The role of Strategic Planning in Crisis Educational Management at Tishreen University from Their worker Perspectives (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research studies the idea of belonging to the place in the introduction of the Omayyad poem . Belonging is a relation that involves emergence and intermingling between the poet and the place . This denotes the special presence in the poet's self according to its different dimensions . The relation of belonging has different aspect and images in the Omayyad poetry , some of which the introductions of the poems that have been , the embodiment of the poet's experiences such as hope, departure and the obssession of returning , etc. because the special belonging is not only a natural one but it is also a social one with its values , customs and traditions . Individuals and the place the interact with it form one unity which the poet belongs to and feels safety , protection and intimacy in it .